THE EFFECT OF DEFERRED TAX EXPENSES, TAX PLANNING AND DEFERRED TAX ASSETS ON EARNINGS MANAGEMENT - Cyndi Khinanti Theis; Zainuddin Zainuddin; Yustiana Djaelani (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this study is to determine and analyze the effect of deferred tax expense, tax planning and deferred tax assets on earnings management. The objects of this research are mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. Sampling using purposive sampling technique obtained 14 companies according to the specified criteria so that a total sample of 82 samples was obtained. The test tool used is panel data regression analysis using the Eviews 12 test tool. The results of this study indicate that: (1) deferred tax expense has no effect on earnings management, (2) tax planning has no effect on earnings management, and (3) deferred tax assets have a negative effect on earnings management.